2021
DOI: 10.3389/fneur.2021.785529
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Programming Time and Strong Symptom Control Even in Chronic Course Through Imaging-Based DBS Programming

Abstract: Objectives: Deep brain stimulation (DBS) programming is based on clinical response testing. Our clinical pilot trial assessed the feasibility of image-guided programing using software depicting the lead location in a patient-specific anatomical model.Methods: Parkinson's disease patients with subthalamic nucleus-DBS were randomly assigned to standard clinical-based programming (CBP) or anatomical-based (imaging-guided) programming (ABP) in an 8-week crossover trial. Programming characteristics and clinical out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 17 publications
1
27
0
Order By: Relevance
“…For instance, Pavese et al (2020) suggested current amplitudes that required adjustments in most of their patients. In contrast, Lange et al (2021) did not use VTA estimations. In their view, these estimations made simplifying assumptions that would not adequately reflect the complexity of stimulated brain tissue.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…For instance, Pavese et al (2020) suggested current amplitudes that required adjustments in most of their patients. In contrast, Lange et al (2021) did not use VTA estimations. In their view, these estimations made simplifying assumptions that would not adequately reflect the complexity of stimulated brain tissue.…”
Section: Discussionmentioning
confidence: 94%
“…Imaging-guided suggestions can help reduce the time needed to program directional leads. For instance, Lange et al (2021) reported an average of 20 min with imaging-guided programming compared to an average of 45 min with traditional programming for a patient implanted bilaterally with directional leads. Of note, they used the visualization in Guide XT to preselect a contact that faced the dorsolateral subthalamic nucleus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The postoperative detection of electrode positions is essential for several aspects, such as to verify the implanted electrode position, to evaluate therapeutic and adverse effects of DBS, and to facilitate and guide stimulation programming [ 4 ]. Segmented contacts of a directional electrode may allow the stimulation field to be generated in a desired direction, so this technology also requires knowledge of the precise electrode orientation in the brain to fully realize its benefits.…”
Section: Discussionmentioning
confidence: 99%
“…While DBS is most commonly used to treat movement disorders, such as Parkinson’s disease and essential tremor, it is increasingly being investigated for its therapeutic potential regarding a range of other brain diseases, including conditions such as neuropathic pain and epilepsy. Estimating the volume of tissue activated (VTA) has demonstrated clinical advantages in programming efficacy [ 4 ] and provides a method for optimizing stimulation while avoiding side effects. Conventional DBS electrodes, which have a linear array of ring contacts, offer limited control over an approximately spherical VTA.…”
Section: Introductionmentioning
confidence: 99%